Stalin's master narrative : a critical edition of the History of the Communist Party of the Soviet Union (Bolsheviks) : short course - Brandenberger, David; Zelenov, M. V. (Mikhail Vladimirovich) (Annals of Communism., 2019)
"A critical edition of the text that defined communist party ideology in Stalin's Soviet Union. The Short Course on the History of the Communist Party of the Soviet Union (Bolsheviks) defined Stalinist ideology both at home and abroad. It was quite literally the the master narrative of the USSR--a hegemonic statement on history, politics, and Marxism-Leninism that scripted Soviet society for a generation. This study exposes the enormous role that Stalin played in the development of this all-important text, as well as the unparalleled influence that he wielded over the Soviet historical imagination."--